Identification of the advection-diffusion equation for predicting green water propagation. (15th October 2020) - Hernández-Fontes, J.V.; Torres, L.; Mendoza, E.; Escudero, M.
Abstract: This paper presents an approach that involves the advection-diffusion equation together with a parameter identification approach to analyze the evolution of consecutive green water events. The goal of the parameter identification approach is the estimation of the AD coefficients in real-time by using a method based on a bank of state estimators, which in turn are based on a spatial-discrete version of the AD equation. In order to test the approach with real data, laboratory experiments of consecutive green water events on a fixed structure were performed. Such events were generated with regular waves of different steepness in a wave flume by employing high-speed video to capture flow evolution. Time series of water elevations were obtained at several positions over the deck to perform the parameter identification and to validate the present approach. Results suggested that the present approach allowed capturing acceptably the evolution of consecutive events even when considering constant AD parameters. Maximum elevations in each event as well as their time of occurrence were well approximated, which is an advantage against traditional analytical methods. Highlights: Evolution of consecutive green water events described by the advection-diffusion (AD) equation. Experimental measurements of spatial and temporal evolution of green water on a fixed structure in regular wave trains. Estimation of the AD coefficients in real-time by using a method based on a bank of state estimators. A convolution model, solution of the AD equation, captures trends and maximum elevations in consecutive green water events.